2011
DOI: 10.1038/ki.2011.226
|View full text |Cite
|
Sign up to set email alerts
|

No difference between alfacalcidol and paricalcitol in the treatment of secondary hyperparathyroidism in hemodialysis patients: a randomized crossover trial

Abstract: Alfacalcidol and paricalcitol are vitamin D analogs used for the treatment of secondary hyperparathyroidism in patients with chronic kidney disease, but have known dose-dependent side effects that cause hypercalcemia and hyperphosphatemia. In this investigator-initiated multicenter randomized clinical trial, we originally intended two crossover study periods with a washout interval in 86 chronic hemodialysis patients. These patients received increasing intravenous doses of either alfacalcidol or paricalcitol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 47 publications
3
58
0
2
Order By: Relevance
“…Conventionally, fracture risk is associated with both high and low levels of PTH (20), but a recent large study showed no relationship below 900 ng/L. The present review is in accordance with the KDOQI guidelines (1) and recommends an upper limit of 300 ng/L, primarily using active vitamin D. There are no proven differences between the various drugs available (21) can be treated with cinacalcet, a calcimimetic, which reduces PTH by about 40%, even in patients with severe secondary hyperparathyroidism. For the elderly patient, medical treatment is preferred to surgical parathyroidectomy.…”
Section: Parathyroid Hormonesupporting
confidence: 58%
“…Conventionally, fracture risk is associated with both high and low levels of PTH (20), but a recent large study showed no relationship below 900 ng/L. The present review is in accordance with the KDOQI guidelines (1) and recommends an upper limit of 300 ng/L, primarily using active vitamin D. There are no proven differences between the various drugs available (21) can be treated with cinacalcet, a calcimimetic, which reduces PTH by about 40%, even in patients with severe secondary hyperparathyroidism. For the elderly patient, medical treatment is preferred to surgical parathyroidectomy.…”
Section: Parathyroid Hormonesupporting
confidence: 58%
“…Although numerous trials have documented the efficacy of cinacalcet (Sensipar/Mimpara; Amgen Inc., Thousand Oaks, CA) (1-10) and vitamin D analogs (11)(12)(13)(14)(15)(16)(17) in lowering PTH levels, no trial to date has directly compared these agents in the treatment of SHPT.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experimental study using different doses of active vitamin D demonstrated that both calcitriol and paricalcitol in high doses stimulated the development of vascular calcification whereas lower doses were protective [9] . Recent study in hemodialysis patients also revealed similar incidence of hypercalcemia and hyperphosphatemia in patients who received alfacalcidol and paricalcitol [36] . In a 2-year observational study in chronic hemodialysis patients, those who received higher prescribed dose of alfacalcidol experienced a slower rate of progression of aortic arch calcification [37] .…”
Section: Active Vitamin Dmentioning
confidence: 85%